2011
DOI: 10.1080/10803548.2011.11076877
|View full text |Cite
|
Sign up to set email alerts
|

Hand Injury From Powered Wood Splitters: Machine Safety, Patterns of Use and Injury Events

Abstract: Introduction.log splitter non-intentional injury consumer product related injury occupational injury agricultural injury injury prevention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We found that hand injuries related to wood splitting were non-occupational traumas and these results are consistent with previous reports. For example, Lindqvist et al reported that 7% of the incidents caused by wood splitters occurred during employment, while 85% occurred during the patient’s leisure time [ 7 ]. Furthermore, in the United States, power-tool use was a risk factor for hand amputation in non-occupational use among men aged 55 years and older [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that hand injuries related to wood splitting were non-occupational traumas and these results are consistent with previous reports. For example, Lindqvist et al reported that 7% of the incidents caused by wood splitters occurred during employment, while 85% occurred during the patient’s leisure time [ 7 ]. Furthermore, in the United States, power-tool use was a risk factor for hand amputation in non-occupational use among men aged 55 years and older [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another database study from the United States, 2.8% of patients hospitalized for traumatic finger amputation from 2012 to 2016 were due to wood splitter [ 6 ]. In addition, Lindqvist et al reported that almost half of patients with wood-splitter-related injuries required finger amputations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional technique of processing logs into smaller and handier firewood has been at the base of Countries development for centuries, as it represents a fundamental source of fuel for energy. The current increasing dynamism of the firewood market has led to the development and improvement of technologies able to process wood more efficiently by reducing consistently the time and labour required for firewood production (Lindroos, 2008;Loibneggar, 2011), as well as the risk of injuries for operators (Lindroos et al, 2008;Lindqvist and Nilsson, 2011). This was done by designing machinery with high productivity and ergonomics standards, able to process logs with a wide range of diameters and dimensions and maintaining as low as possible the production costs, even if the total capital investment became higher if related to simpler traditional methods.…”
Section: Introductionmentioning
confidence: 99%